TALAK PERSPEKTIF PERBANDINGAN MADZHAB - Arofik, Slamet; Aliftus Sholichah, Binti (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2024)
Talaq is the annihilation of the marriage bond or part of the marriage bond,the marriage bond becomes completely non-existent if there are threedivorces (talak ba'in), and if only one divorce is imposed (talak raj'i) then whatis abolished is part of the marriage bond. If a marriage has occurred, whatmust be avoided is divorce. The stronger a person's efforts in building theirhousehold, the easier it is for them to avoid divorce. Divorce brings harm,while something that brings harm must be avoided. With divorce, not onlyhusband and wife become victims, but also their children. The permissibilityof talaq is because the dynamics of household life sometimes lead tosomething that is contrary to the purpose of forming the household. In asituation that is no longer reconcilable, if family life continues it will causeharm to both parties and the people around them. In order to avoid furtherharm, it is better to pursue divorce in the form of talaq. Thus, talaq in Islam isonly for a beneficial purpose.